2018
DOI: 10.1038/s41467-018-06666-4
|View full text |Cite
|
Sign up to set email alerts
|

Divergent wiring of repressive and active chromatin interactions between mouse embryonic and trophoblast lineages

Abstract: The establishment of the embryonic and trophoblast lineages is a developmental decision underpinned by dramatic differences in the epigenetic landscape of the two compartments. However, it remains unknown how epigenetic information and transcription factor networks map to the 3D arrangement of the genome, which in turn may mediate transcriptional divergence between the two cell lineages. Here, we perform promoter capture Hi-C experiments in mouse trophoblast (TSC) and embryonic (ESC) stem cells to understand h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 57 publications
3
56
0
Order By: Relevance
“…Strikingly, these experiments revealed that following reprogramming, ESC-specific contacts became more frequent at genes related to developmental processes, the formation of which preceded changes in transcription (Stadhouders et al 2018). In support of this finding, another study, using a technique called promoter capture Hi-C, found that developmental pathway-related genes are enriched in ESC-specific promoterenhancer interactions; a large amount of distinct cell-type-specific contacts were detected for both ESCs and fetal liver cells at promoters interacting with more than 10 enhancers (Schoenfelder et al 2018).…”
Section: Chromatin Loops Domains and Interaction Hubsmentioning
confidence: 82%
“…Strikingly, these experiments revealed that following reprogramming, ESC-specific contacts became more frequent at genes related to developmental processes, the formation of which preceded changes in transcription (Stadhouders et al 2018). In support of this finding, another study, using a technique called promoter capture Hi-C, found that developmental pathway-related genes are enriched in ESC-specific promoterenhancer interactions; a large amount of distinct cell-type-specific contacts were detected for both ESCs and fetal liver cells at promoters interacting with more than 10 enhancers (Schoenfelder et al 2018).…”
Section: Chromatin Loops Domains and Interaction Hubsmentioning
confidence: 82%
“…5a-b). To understand the DMR epigenetic signature in a developmental context, published ChIP-seq data sets in spermatozoa 37 , and wildtype embryonic stem cell (ESC) 42,43 and trophoblast stem cell (TSC) [44][45][46] lines were assessed. In TSCs, histone marks at all three DMRs were largely absent ( Fig.…”
Section: Epigenetic Memory Of Sperm Dmrsmentioning
confidence: 99%
“…Epigenetic signature of the intragenic Cwc27 DMR in wildtype ESCs, TSCs and spermatozoa. Enrichment of DNA binding proteins (TET1, CTCF, PRM1, H3) and histone modifications (H3K27ac, H3K27me3, H3K4me1, H3K4me3, H3K9me3) in the Cwc27 locus on Chr13 (~37,000 kb downstream of Mtrr gene) using published ChIP-seq data sets in wildtype embryonic stem cells (ESCs), trophoblast stem cells (TSCs) 42 , and spermatozoa (Sp) 37 . Tn5 transposase sensitive sites (THSS) were also determined using published ATAC-seq data sets of normal B6D2F1 mouse epiblast and extraembryonic ectoderm (ExE) at embryonic day 6.5 38 or normal CD1 spermatozoa 37 .…”
Section: Nucleicmentioning
confidence: 99%
See 1 more Smart Citation
“…This disregards 3D genome conformation, which enables long-range interactions and is not restricted to one-to-one relationships between TEs and genes. We therefore coupled TE+ enhancers to genes they putatively regulate based on promoter capture Hi-C (PCHi-C) data that we recently generated in ESCs and TSCs (Schoenfelder et al 2018). Only 34-44% of TE+ enhancers interacted with at least one gene promoter, which was nonetheless higher than the proportion of non-enhancer TEs with gene promoter interactions (21-28%, Supplementary Figure 4A).…”
Section: Te-derived Enhancers Interact With Lineage-specific Genesmentioning
confidence: 99%